Human monitoring, smart health and assisted living : techniques and technologies - Longhi, S.; Monteriù, Andrea; Freddi, Alessandro (IET healthcare technologies series, 2017)
The book is composed of the following chapters: Personal monitoring and health data acquisition in smart homes; Contactless monitoring of respiratory activity using electromagnetic waves for ambient assisted living framework: feasibility study and prototype realization; Technology-based assistance of people with dementia: state of the art, open challenges, and future developments; Wearable sensors for gesture analysis in smart healthcare applications; Design and prototyping of an innovative home automation system for the monitoring of elderly people; Multi-sensor platform for circadian rhythm analysis; Smart multi-sensor solutions for ADL detection; Comprehensive human monitoring based on heterogeneous sensor network; Ambient intelligence for health: advances in vital signs and gait monitoring systems within mHealth environments; and Smartphone-based blood pressure monitoring for falls risk assessment: techniques and technologies.